C.R. Van Norman correspondence - Van Norman, C. R.
ALsS (1861 July 4 and September 19) written by Van Norman to his aunt describing camp life and training during his Civil War service with the 4th Wisconsin Infantry Regiment in Maryland and Pennsylvania.
Union soldier.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Army -- Military life; United States. -- Army. -- Wisconsin Infantry Regiment, 4th (1861-1863); Maryland -- History -- Civil War, 1861-1865.; Pennsylvania -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; Wisconsin -- History -- Civil War, 1861-1865.; Soldiers